2020
DOI: 10.1007/s11596-020-2166-4
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of CARD9 in Metabolic Diseases

Abstract: Caspase recruitment domain containing protein 9 (CARD9) is an adaptor protein that plays a critical role in pattern recognition receptors (PRRs)-mediated activation of NF-κB and mitogen-activated protein kinase (MAPK). This elicits initiation of the pro-inflammatory cytokines and leads to inflammatory responses, which has been recognized as a critical contributor to chronic inflammation. Current researches demonstrate that CARD9 is strongly associated with metabolic diseases, such as obesity, insulin resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…It has been well established that excessive inflammation, ROS production and related oxidative stress significantly contribute to CVDs, including atherosclerosis, cardiac fibrosis, coronary artery disease, myocardial infarction, and heart failure ( 4 , 6 , 86 , 149 ). CARD9-mediated signaling in CVDs has been well documented in several reviews ( 4 , 16 , 150 ). Briefly, CARD9-mediated production of cytokines and chemokines results in cardiovascular dysfunction by instigating a positive feedback loop of inflammation and oxidative stress.…”
Section: Card9 and Diseasesmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been well established that excessive inflammation, ROS production and related oxidative stress significantly contribute to CVDs, including atherosclerosis, cardiac fibrosis, coronary artery disease, myocardial infarction, and heart failure ( 4 , 6 , 86 , 149 ). CARD9-mediated signaling in CVDs has been well documented in several reviews ( 4 , 16 , 150 ). Briefly, CARD9-mediated production of cytokines and chemokines results in cardiovascular dysfunction by instigating a positive feedback loop of inflammation and oxidative stress.…”
Section: Card9 and Diseasesmentioning
confidence: 98%
“…Reactive oxygen species (ROS) formation and oxidative stress are closely related to the development and progression of a variety of diseases including infection, inflammatory diseases, tumors, and cardiovascular diseases (CVDs) ( 12 14 ). The critical roles of CARD9 in cytokines/chemokines secretion and ROS production in different cells and organ systems naturally connect CARD9 with the disease conditions associated with ROS and inflammation ( 4 , 9 , 15 , 16 ). Mutation and genetic polymorphisms of CARD9 are reported to be correlated with a wide range of infectious diseases in human ( 17 – 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, CARD9 also plays a role in both infectious and non-infectious pathophysiological processes of heart injuries, including myocarditis, myocardial ischemia reperfusion (I/R) injury, and angiotensin II (Ang II)-induced cardiac remodeling and dysfunction 10 - 12 . Previously, Tian et al summarized the proinflammatory role of CARD9 in metabolic diseases, including insulin resistance and obesity, which are the risk factors of CVDs, and in heart diseases 13 . In contrast, we focus on the various potential roles of CARD9 in CVDs from different perspectives based on recent studies.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have shown that global CARD9-deficient mice are resistant to developing viral myocarditis, cardiac hypertrophy, or vein graft failure. 3 CARD9 expression is significantly increased in viral myocarditis, and CARD9 deficiency prevents Coxsackie virus B3-induced excessive inflammation and production of transforming growth factor-β (TGF-β), IL-17A, and BCL-10 in mouse myocardium, with decreased serum levels of IL-6, IL-10, IFN-γ, TGF-β, and IL-17A. Angiotensin II and transverse aortic constriction markedly increase CARD9 expression in the mouse heart.…”
mentioning
confidence: 99%
“…High-fat diet and zinc deficiency-induced oxidative stress activate CARD9/p38 MAPK signaling, an important mechanism for obesity-related cardiac hypertrophy. 3 Zinc supplement suppresses CARD9 expression and reduces oxidative stress in mice on a high-fat diet. CARD9 expression and production of proinflammatory cytokines are increased in vein grafts and associated with graft macrophage infiltration and neointima formation.…”
mentioning
confidence: 99%